Anti-Angiogenic Alternative and Complementary Medicines for the Treatment of Endometriosis: A Review of Potential Molecular Mechanisms. (1st October 2018) - Zheng, Weilin; Cao, Lixing; Xu, Zheng; Ma, Yuanyuan; Liang, Xuefang
Abstract : Endometriosis is caused by the growth or infiltration of endometrial tissues outside of the endometrium and myometrium. Symptoms include pain and infertility. Surgery and hormonal therapy are widely used in Western medicine for the treatment of endometriosis; however, the side effects associated with this practice include disease recurrence and menopause, which can severely influence quality of life. Angiogenesis is the main biological mechanism underlying the development of endometriosis. Numerous natural products and Chinese medicines with potent anti-angiogenic effects have been investigated, and the molecular basis underlying their therapeutic effects in endometriosis has been explored. This review aims to describe natural products and compounds that suppress angiogenesis associated with endometriosis and to assess their diverse molecular mechanisms of action. Furthermore, this review provides a source of information relating to alternative and complementary therapeutic products that mediate anti-angiogenesis. An extensive review of the literature and electronic databases, such as the China National Knowledge Infrastructure, PubMed, and Embase, was conducted using the keywords 'endometriosis, ' 'traditional Chinese medicine, ' 'Chinese herbal medicine, ' 'natural compounds, ' and 'anti-angiogenic' therapy. Anti-angiogenic therapy is an emerging strategy for the treatment of endometriosis. Natural anti-angiogenic products and Chinese medicines provide several beneficial clinical effects, including pain relief. In this review, we summarize clinical trials and experimental studies of endometriosis using natural products and Chinese medicines. In particular, we focus on anti-angiogenic products and alternative and complementary medicines for the treatment of endometriosis and additionally examine their therapeutic efficacy and mechanisms of action. Anti-angiogenic natural products and/or compounds provide a new approach for the treatment of endometriosis. Future work will require randomized trials with larger numbers of subjects, as well as long-term follow-up to confirm the findings described here.